Japan's role in Asian development: lessons for Sri Lanka - Weerakoon, Dushni; Ratwatte, Lekha; Institute of Policy Studies (Colombo, Sri Lanka) (Colombo, Sri Lanka : Institute of Policy Studies, 1996)
With reference to South Asia in general and Sri Lanka in particular.
Includes bibliographical references (p. 40-41).
Microfiche.
Keywords: Japan -- Foreign economic relations -- Sri Lanka; Sri Lanka -- Foreign economic relations -- Japan; Japan -- Foreign economic relations -- South Asia; South Asia -- Foreign economic relations -- Japan